Titanium and Vanadium Complexes as Anticancer Agents - Kostova, Irena (Anti-Cancer Agents in Medicinal Chemistry, 2009)
A series of complexes containing titanium and vanadium as a metal centers have shown to possess a wide spectrum of antitumor properties. These series belong to the non-platinum metal antitumor agents that appear to offer a different alternative for cancer chemotherapy which do not follow mechanism of action of the platinum complexes. The antitumor activity of both titanocene and vanadocene complexes has been established against various animal and xenografted human tumors. The exact mechanism of action for these compounds has not been determined, the target is unknown and even the exact chemical nature of the formulated solutions is still unknown. It has been proposed that these species interact with DNA, inhibiting the cell cycle. However, the antitumor mechanism of the titanocenes is most likely a complex pathway, probably involving a number of different biological molecules related to the transport and delivery of Ti species into cancer cells, and, after hydrolysis, subsequent interaction with nucleic acids and/or proteins and/or other potential coordinating constituents present in the intracellular environment. The tendency to hydrolyze seems to be one of the hypotheses for the tumor-inhibiting potency of the titanocene dihalides. Vanadium compounds exert preventive effects against chemical carcinogenesis on animals, by modifying, mainly, various xenobiotic enzymes, inhibiting, thus, carcinogen-derived active metabolites. The anticarcinogenic effects of vanadium, in combination to its low toxicity, established also, by its administration in humans, suggest vanadium as a candidate antineoplastic agent against human cancer. New complexes being more potent and less toxic favor this perspective. The use of these species as chemotherapeutic agents remains relatively unexplored and waits for future investigation. Research proceeded during the recent decades, enriched our knowledge on the chemical and biochemical properties, as well as the mechanisms of systemic, cellular and molecular antitumor effects of titanium and vanadium compounds.
Keywords: tumor cell lines